Strategi Implementasi Prinsip Fikih dalam Lembaga Kuangan Syariah di Indonesia - Ayunda Sausan Ramadanti; Ahmad Mu’is; Khansa Putri Nalita (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This study aims to explore how fiqh principles are applied in the operations of Islamic financial institutions in Indonesia. Fiqh principles, which form the basis of Islamic law, serve as guidelines for financial contracts and transactions, ensuring they comply with Islamic law and Islamic values. The qualitative method used focuses on literature review and analysis of the implementation of fiqh principles in contracts such as mudharabah, musyarakah, murabahah, and other contracts. The findings of this study indicate that the application of fiqh principles in Islamic financial institutions not only improves product halal certification and transaction transparency but also strengthens customer trust and institutional stability through Sharia-compliant risk management. Successful strategy implementation includes maintaining internal regulations, staff training, consultation with fiqh experts, and ongoing supervision to maintain operational integrity. Thus, Islamic financial institutions in Indonesia can grow sustainably and provide broad benefits to society in accordance with Sharia principles.